A needs analysis to develop new curriculum for Korean college students in higher education - Eunjeong Park (Universitas Pendidikan Indonesia, 2022)
Language teachers and instructors should always consider how to successfully develop new curricula. A medium-sized university in Korea launched a new liberal arts course for freshmen. A language instructor conducted a need analysis to understand the needs of college students to develop a new curriculum of the assigned course. The purpose of this study is to examine the needs of Korean university students who learn English to develop new curriculum and instruction reflecting learner needs accordingly. Data were collected through interviews and survey questionnaires. The qualitative data of the interview went through a thematic analysis process, and the quantitative data of the survey were analysed through statistical tests. As a result, various perspectives of students were revealed. First, this study showed that competency-based language instruction is essential for learners’ language development. Second, skill integration was needed to improve language skills. Third, the students expected constructive feedback from the instructor on their English grammar and vocabulary use. This study presents the significance of performing needs analysis and suggests that language teachers should consider it for their professional development and growth in higher education.